Impact of a modified implant macrogeometry on biomechanical parameters and bone-related markers in rats - Mounir Colares MUSSI; Fernanda Vieira RIBEIRO; Monica Grazieli CORRÊA; Cristiane Ribeiro SALMON; Suzana Peres PIMENTEL; Fabiano Ribeiro CIRANO; Marcio Zaffalon CASATI (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract This study investigated the impact of a modified implant macrogeometry on peri-implant healing and its effect on bone-related molecules in rats. Eighteen rats received one implant in each tibia: the control group received implants with conventional macrogeometry and the test group received implants with modified macrogeometry. After 30 days, the implants were removed for biomechanical analysis and the bone tissue around them was collected for quantifying gene expression of OPN, Runx2, β-catenin, BMP-2, Dkk1, and RANKL/OPG. Calcein and tetracycline fluorescent markers were used for analyzing newly formed bone at undecalcified sections of the tibial implants. These fluorescent markers showed continuous bone formation at cortical bone width and sparse new bone formed along the medullary implant surface in both groups. However, higher counter-torque values and upregulation of OPN expression were achieved by test implants when compared to controls. The modified macrogeometry of implants optimized peri-implant healing, favoring the modulation of OPN expression in the osseous tissue around the implants.